Pengaruh Pupuk Organik Berbahan Dasar Cairan Flushing Kandang Terhadap Pertumbuhan Rumput Raja (Pennisetum purpoides L.) - Nadia Nuraniya Kamaluddin; Rija Sudirja; Eso Solihin; Suryo Firnato (Soilrens, 2019)
Dairy farming waste in high volume especially in the form of flushing slurry can be unmanageable. Flushing slurry is lower in organic matter content compared to solid waste due to water saturation. In order to enhance the utilization, flushing slurry can be converted in liquid organic fertilizer with higher nutrient content. King grass (Pennisetum purphoides L.) plant is commonly used as livestock feed especially dairy cow in South Bandung area. The experiment was conducted between March to June 2018 in Pangalengan, South Bandung. The result shows no significant different between control specimen and liquid organic fertilizer teratments in plant hight, number of leaves, root weight, and root length. Although notable amount of plant leaves was demonstrated in D treatment compared to than that of control.